Proceedings of the 10th Annual Conference on Genetic and Evolutionary Computation 2008
DOI: 10.1145/1389095.1389204
|View full text |Cite
|
Sign up to set email alerts
|

A study of NK landscapes' basins and local optima networks

Abstract: We propose a network characterization of combinatorial fitness landscapes by adapting the notion of inherent networks proposed for energy surfaces [5]. We use the well-known family of NK landscapes as an example. In our case the inherent network is the graph where the vertices are all the local maxima and edges mean basin adjacency between two maxima. We exhaustively extract such networks on representative small NK landscape instances, and show that they are 'small-worlds'. However, the maxima graphs are not r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
112
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

8
2

Authors

Journals

citations
Cited by 151 publications
(116 citation statements)
references
References 21 publications
(40 reference statements)
4
112
0
Order By: Relevance
“…Local optima networks (LONs) [9] model the global structure of landscapes as graphs where nodes are local optima and edges represent possible transitions among them with a given search operator. In order to model GI tness landscapes with local optima networks, we adapted the model with escape edges [16].…”
Section: Local Optima Networkmentioning
confidence: 99%
“…Local optima networks (LONs) [9] model the global structure of landscapes as graphs where nodes are local optima and edges represent possible transitions among them with a given search operator. In order to model GI tness landscapes with local optima networks, we adapted the model with escape edges [16].…”
Section: Local Optima Networkmentioning
confidence: 99%
“…GECCO '16, July 20 -24, 2016, Denver, CO, USA Ochoa et al [24] propose to characterize funnels in combinatorial spaces using local optima networks (LONs, [22]). The idea of LONs was inspired by the study of energy landscapes [28], and it was found that energy landscapes often have a structure of multiple funnels as well [19].…”
Section: Introductionmentioning
confidence: 99%
“…This article uses the Local Optima Network (LON) model [15,16,14,18] in order to explore in more detail the structure of TSP landscapes near the global optimum. Local optima networks compress the whole search spaces into a graph having as vertices the local optima, and as edges transitions among them according to a given search operator.…”
Section: Introductionmentioning
confidence: 99%